Collaborative Language Learning Practices of Teachers in ELT Classroom - Bhandari, Bhim Lal (Lumbini Journal of Language and Literature, 2022)
This study aims to explore the collaborative language teaching practices of English teachers in ELT classrooms in Nepal. Applying the theoretical framework of social constructivism, I used narrative inquiry to explore my participants’ stories regarding their practices of collaborative teaching in English classrooms. Two secondary-level English teachers from two community schools in Rupandehi district were purposively selected. I interviewed them using a semi-structured interview to elicit relevant information. This study reveals that the teacher participants felt positive toward collaborative practices to construct new knowledge, bring a solution to problems and make learning successful. The study also reveals that English teachers and learners working together sharing and exchanging ideas develop mutual trust and respect for each other. In addition, it helps establish a social atmosphere conducive to meaningful learning and to solving students’ problems.